Social Influences on Prevotella and the Gut Microbiome of Young Monkeys. Issue 8 (October 2017) - Amaral, Wellington Z.; Lubach, Gabriele R.; Proctor, Alexandra; Lyte, Mark; Phillips, Gregory J.; Coe, Christopher L.
ABSTRACT: Objective: Our aim was to evaluate the bacterial profiles of young monkeys as they were weaned into peer groups with a particular focus on Prevotella, an important taxon in both human and nonhuman primates. The weaning of infants and increased social contact with peers is a developmental stage that is likely to affect the gut microbiome. Methods: Gut bacteria were assessed in 63 rhesus monkeys living in social groups comprised of 4 to 7 individuals. Two groups were assessed prospectively on day 1 and 2 weeks after rehousing away from the mother and group formation. Ten additional groups were assessed at 2 weeks after group establishment. Fecal genomic DNA was extracted and 16S ribosomal RNA sequenced by Illumina MiSeq (5 social groups) and 454-amplicon pyrosequencing (7 social groups). Results: Combining weaned infants into small social groups led to a microbial convergence by 2 weeks ( p < .001). Diversity analyses indicated more similar community structure within peer groups than across groups ( p < .01). Prevotella was the predominant taxon, and its abundance differed markedly across individuals. Indices of richness, microbial profiles, and less abundant taxa were all associated with the Prevotella levels. Functional Kyoto Encyclopedia of Genes and Genomes analyses suggested corresponding shifts in metabolic pathways. Conclusions: The formation of small groups of young rhesus monkeys was associated with significant shifts in the gut microbiota. The profiles were closely associated with the abundance of Prevotella, a predominant taxon in the rhesus monkey gut. Changes in the structure of the gut microbiome are likely to induce differences in metabolic and physiologic functioning. Abstract : Supplemental digital content is available in the text.